The biological meaning of anti-HBC positive result in blood donors: relation to HBV-DNA and to other serological markers - Arraes, Luiz C.; Ximenes, Ricardo; Andrieu, Jean-marie; Lu, Wei; Barreto, Silvana; Pereira, Leila M.m.b.; Castelo, Adauto [UNESP] (Instituto de Medicina Tropical, 2003)
In order to assess the potential risk of anti-HBc-positive blood donors for post-transfusional hepatitis and to investigate whether other HBV serological markers are capable of identifying the presence of the virus, 1000 first-time blood donors were enrolled between June and July 1997. These donors were screened using routine Brazilian blood center tests (HIV 1 and 2, HTLV 1 and 2, Chagas disease, Syphilis, HCV, HBsAg, anti-HBc and ALT ). The 120 (12%) found to be anti-HBc-positive underwent further tests: HBe, anti-HBe, anti-HBs and HBV-DNA by PCR. Ten cases were HBsAg positive and all were HBV-DNA positive by PCR. Three HBsAg-negative donors were HBV-DNA-positive. Two HBV-DNA-positive donors were also anti-HBs-positive. All the HBV-positive donors had at least one HBV marker other than anti-HBc. Anti-HBc is an important cause of blood rejection. Testing for HBsAg alone is not fully protective and anti-HBc remains necessary as a screening test. The presence of anti-HBs is not always indicative of absence of the virus. The addition of other HBV serological markers could represent an alternative in predicting the presence of the virus when compared with PCR. It is recommended that other studies should be carried out to confirm this finding.

Para verificar o risco potencial para hepatite viral pós-transfusional de doadores anti-HBc positivos e investigar se outros marcadores sorológicos do HBV poderiam identificar a presença ou não do vírus, mil doadores de primeira vez foram recrutados entre junho e julho de 1997. Estes doadores foram testados para os testes de rotina utilizados em centros de transfusão brasileiros. Cento e vinte desses doadores foram anti-HBc positivos (12%). Nestes foram realizados os testes HbeAg, anti-HBc, anti-HBs e a pesquisa do HBV-DNA por PCR. Dez eram HbsAg positivos, todos com presença do HBV-DNA demonstrada por PCR. Três doadores HbsAg negativos foram HBV-DNA positivos. Dois doadores HBV-DNA positivos também o foram para o anti-HBs. Todos os doadores HBV positivos apresentavam pelo menos outro marcador sorológico do HBV, além do anti-HBc. O anti-HBc é uma importante causa de descarte de sangue. A pesquisa isolada do HbsAg não é completamente protetora e a presença do anti-HBc permanece necessária como teste de triagem. A presença do anti-HBs não é sempre indicativa da ausência do vírus. A adição de outros marcadores pode ser uma alternativa para predizer a presnça do vírus quando comparada com a PCR. Outros estudos, no entanto, devem ser conduzidos para confirmar este achado.
Significado biológico do resultado anti-HBc positivo em doadores de sangue: relação com HBV-DNA e outros marcadores sorológicos
Keywords: Hepatitis B; Transfusion; Serological markers; HBV-DNA